Biofeedback on eretic disfunction and quality of life in post radical prostatectomy patients: a systematic review (Research, Society and Development, 2023)
Prostate cancer is the most prevalent cancer in the male population, and although the gold standard treatment is radical prostectomy, it is common for unwanted effects to arise, such as erectile dysfunction and emotional problems. A tool that helps in the treatment of erectile dysfunction is the biofeedback, which acts through the visualization and recording of pelvic floor muscle contractions. The objective of this systematic review was to investigate if biofeedback improves erectile function and quality of life in patients after radical prostatectomy. Articles were searched in the databases PUBMED, LILACS, PEDro, and SCIELO, using the descriptors "erectile dysfunction", "quality of life" and "prostatectomy". Throughout the study, it was observed that the use of biofeedback probably reveals a positive effect on erectile function, and may significantly interfere with the quality of life of the study population. We suggested, therefore, the production of more articles due to the scarce number of interventional studies on the theme.